Antibacterial evaluation of Dalbergia latifolia (Roxb.) liquid smoke used for the treatment of bovine mastitis - Patel, Tej; Patel, Kalpesh; Patel, Ridhdhi (Current Botany, 2025)
The indigenous people of the area have long utilized medicinal plants to treat bovine mastitis. Traditional ethnoveterinary healers used plant-based techniques to treat diseased cows. Escherichia coli and Coagulase-negative Staphylococci (CoNS) bacteria infect the udder and cause mastitis, which lowers milk production. In this work condensed smoke of heartwood of Dalbergia latifolia was produced by pyrolysis at 500 °C for 8 hr and filtered with Whatman No.1. The liquid smoke was analysed with GC-MS and found 23 bioactive phytocompounds that have antibacterial activity of mastitis causing bacteria E. coli and CoNS. The antibacterial activity was carried out using disc diffusion methods with three different concentrations of liquid smoke which were 150 μL/mL, 300 μL/mL and 600 μL/mL of distilled water. The maximum inhibition average of 21.00 mm at 600 μL/mL treatment E. coli (S1) and 28.33 mm at 600 μL/mL on E. coli (S2), the positive control average value of 15.88 mm and 0.00 mm in E. coli (S1) and E. coli (S2) respectively. The maximum inhibition of 20 mm of CoNS average value 2 of 4.66 mm was estimated at 600 μL/mL treatments. The Ampicillin antibiotics disc was used to have a positive control for all the treatment. The liquid smoke of D. latifolia has higher antibacterial properties to cure mastitis disease in dairy cows.